Self-etching primers vs acid conditioning: Impact on bond strength between ceram ics and resin cement - Tribst, J. P.M. [UNESP]; Anami, L. C.; Özcan, M. [UNESP]; Bottino, M. A. [UNESP]; Melo, R. M. [UNESP]; Saavedra, G. S.F.A. (Operative Dentistry, 2018)
This study tested whether a self-etching surface agent and the conventional hydrofluoric acid (HF) would provide the same bonding capacity between resin cement and feldspathic (Fd) and lithium disilicate (Ld) ceramics. Ceramic blocks were cut with a low-speed diamond saw with water cooling (Isomet 1000, Buehler, Lake Bluff, IL, USA) into 20 blocks of 5 3 7 3 4 mm, which were ground flat in a polishing machine (EcoMet/AutoMet 250, Buehler) under water cooling. The blocks were randomly divided into eight groups (n=5), according to ceramic type (Ld or Fd), surface conditioning (HF + Monobond Plus or Etch and Prime), and aging by thermocycling (TC or absence-baseline). After 24 hours in 378C distilled water, blocks were embedded into acrylic resin and 1-mm2 cross-section beams composed of ceramic/cement/composite were obtained. The microtensile test was performed in a universal testing machine (DL-1000, EMIC, São José dos Campos, Brazil; 0.5 mm.min-1, 50 kgf load cell). Bond strength (MPa) was calcu-lated by dividing the load at failure (in N) by the bonded area (mm2). The fractured specimens were examined under stereomicroscopy, and one representative sample of each group was randomly selected before the cementation and was further used for analysis using scanning electron microscopy (SEM) and energydispersive x-ray spectroscopy (EDS). The selfetching agent showed the highest bond strength for Fd (24.6664.5) and Ld (24.7366.9) ceramics and a decrease in surface wettability. SEM and EDS showed the presence of similar components in the tested materials with different topographies for both. Therefore, the self-etching primer was able to deliver even higher bonding than HF+silane to a resin cement.